2022
DOI: 10.1136/bmjqs-2022-015314
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of serious paediatric conditions in 13 regional emergency departments

Abstract: ObjectiveTo evaluate rates, risk factors and outcomes of delayed diagnosis of seven serious paediatric conditions.MethodsThis was a retrospective, cross-sectional study of children under 21 years old visiting 13 community and tertiary emergency departments (EDs) with appendicitis, bacterial meningitis, intussusception, mastoiditis, ovarian torsion, sepsis or testicular torsion. Delayed diagnosis was defined as having a previous ED encounter within 1 week in which the condition was present per case review. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…While individual studies of both cardiovascular and neurologic symptoms demonstrated diagnostic disparities linked with ethnicity or insurance status, in pooled analysis, no consistent associations were identified. These findings add to the growing evidence base of diagnostic disparities across many clinical conditions such as delayed appendicitis diagnosis in Black children, overdiagnosis of schizophrenia in Black individuals, and delayed dementia diagnosis in Asian and Hispanic/Latinx individuals 4–9…”
mentioning
confidence: 77%
“…While individual studies of both cardiovascular and neurologic symptoms demonstrated diagnostic disparities linked with ethnicity or insurance status, in pooled analysis, no consistent associations were identified. These findings add to the growing evidence base of diagnostic disparities across many clinical conditions such as delayed appendicitis diagnosis in Black children, overdiagnosis of schizophrenia in Black individuals, and delayed dementia diagnosis in Asian and Hispanic/Latinx individuals 4–9…”
mentioning
confidence: 77%
“…We then performed conditional logistic regression with the outcome of possible delayed diagnosis and sole covariate of log 2 pediatric ED volume, conditioned on the matched set. 3 The goal of this matched analysis was to control for condition, CCC, and age, which we believed to be the most important risks for delayed diagnosis. We used log volume to report the relative odds of delayed diagnosis with each 2-fold increase in volume.…”
Section: Discussionmentioning
confidence: 99%
“…In the all-conditions model, we matched each case patient (those with possible delayed diagnoses) to 4 control patients by condition (exact match), CCC (exact match), and age (nearest neighbor matched on continuous age). We then performed conditional logistic regression with the outcome of possible delayed diagnosis and sole covariate of log 2 pediatric ED volume, conditioned on the matched set . The goal of this matched analysis was to control for condition, CCC, and age, which we believed to be the most important risks for delayed diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations